Pengaruh Kemauan Untuk Mencapai Tujuan, Kebutuhan dan Tujuan Dosen dan Hubungan Interpersonal Terhadap Kinerja Dosen Generasi Milenial Universitas Sumatera Utara - Arif Qaedi Hutagalung; Amlys Syahputra Silalahi; Doli Muhammad Ja’far Dalimunthe; Adika Fajar Putra (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This research aims to test the influence of willingness to achieve lecturers' goals, needs and objectives and interpersonal relationships on the performance of millennial lecturers. The population is lecturers in a state university in Indonesia. The data analysis techniques used are multiple linear analysis and descriptive statistical analysis. The results showed that the willingness to achieve lecturers' goals, needs and objectives and interpersonal relationships had a positive and significant influence partially and simultaneously on the performance of millennial lecturers. This research is expected to be used as input for the university to pay attention and fulfil and fully support the needs of millennial lecturers to improve the performance of lecturers.